The End of LIBOR: On Interest Rate Benchmark Reform, Alternative Risk-Free Rates, IBOR Fallbacks, LIBOR Cessation and Transition - Oliver Read; Jochen Beißer (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifin), 2021)
The reform of LIBOR by its administrator IBA to a transaction-based benchmark, completed 2019, has not succeeded due to lack of transactions. In July 2017 the UK FCA Chief Bailey prepared the market for the end of LIBOR by end-2021. National working groups have developed alternatives to LIBOR based on overnight Risk-Free Rates. For derivatives linked to LIBOR and other IBORs, ISDA developed an IBOR Fallbacks approach on the basis of term and spread adjusted Risk-Free Rates. Bloomberg started daily calculations of fallback rates for covered IBORs on 21 October 2020. An ISDA supplement and a protocol for new and legacy derivative contracts became effective on 25 January 2021. A future cessation and loss of representativeness for all LIBOR settings was declared by IBA and the FCA on 5 March 2021 triggering an index cessation event under ISDA. Some USD LIBOR settings will cease mid-2023 instead of end-2021. The FCA will use enhanced powers to produce Synthetic LIBOR for some settings in GBP and JPY LIBOR beyond end-2021. The standard-setting bodies IOSCO and FSB are closely following the impact of LIBOR cessation and transition on systemic risk at the global level.
Keywords: E43; G01; G15; G18; 330; 2006 ISDA Definitions; 2021 ISDA Interest Rate Derivatives Definitions; Interest Rate Benchmark Reform; EURIBOR; exteuroSTR; fallback rates; IBOR; IBOR Fallbacks Protocol; IBOR Fallbacks Supplement; IOSCO Principles for Financial Benchmarks; LIBOR; LIBOR Cessation; LIBOR Transition; Risk-Free Rates (RFRs); Reference rates; SARON; SOFR; SONIA; Term SONIA Reference Rates (TSRR); TONA